2021
DOI: 10.1080/14756366.2021.1984903
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule compounds with good anti-inflammatory activity reported in the literature from 01/2009 to 05/2021: a review

Abstract: Inflammation and disease are closely related. Inflammation can induce various diseases, and diseases can promote inflammatory response, and two possibly induces each other in a bidirectional loop. Inflammation is usually treated using synthetic anti-inflammatory drugs which are associated with several adverse effects hence are not safe for long-term use. Therefore, there is need for anti-inflammatory drugs which are not only effective but also safe. Several researchers have devoted to the research and developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 126 publications
(140 reference statements)
2
11
0
Order By: Relevance
“…Interestingly, compound 7 exhibited the ability to reduce the expression of IL-6 and TNF-α genes compared to celecoxib-treated LPS-activated RAW264.7 cells. Our findings are in accordance with several studies which showed that hydantoins, analogues of thiohydantoins, are potent anti-inflammatory agents by inhibiting TNF-α precursor enzyme [ 4 , 5 , 75 ]. Our results indicate that compound 7 exhibits an efficient anti-inflammatory activity against LPS-activated RAW264.7 cells by suppressing IL-6 and TNF-α cytokines.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Interestingly, compound 7 exhibited the ability to reduce the expression of IL-6 and TNF-α genes compared to celecoxib-treated LPS-activated RAW264.7 cells. Our findings are in accordance with several studies which showed that hydantoins, analogues of thiohydantoins, are potent anti-inflammatory agents by inhibiting TNF-α precursor enzyme [ 4 , 5 , 75 ]. Our results indicate that compound 7 exhibits an efficient anti-inflammatory activity against LPS-activated RAW264.7 cells by suppressing IL-6 and TNF-α cytokines.…”
Section: Resultssupporting
confidence: 93%
“…However, it possesses a set of side effects, mainly gastrointestinal problems. The discovery of new effective anti-inflammatory agents, thus, considered as an urgent concern [ 4 , 5 ]. Several reports demonstrated 2-thioxoimidazolidine-4-one analogues as a potent class of compounds which possess a broad-spectra of pharmacological and biological activities [ 64 , 65 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Imidazole has emerged as an anti-inflammatory agent because of its broad spectrum of in-vitro and in-vivo chemotherapeutic activities. [9][10][11][12][13] the biological activities exhibited by compounds containing imidazole moiety have prompted chemists to synthesis more and more imidazole libraries and screen them for potential activities. Based on these findings, we decided to synthesize some novel imidazole-5(4H)-one derivative by multi-step synthesis and evaluated its in-vivo anti-inflammatory activity with the hope to obtain more active anti-inflammatory agents.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst the third one, microsomal (mPGES‐1), is inducive that is expressed in response to pro‐inflammatory stimuli and is thus responsible for the production of PGE2 after inflammation and hence the induction of all the inflammatory responses (Gomez et al, 2013; Gurusamy et al, 2021; Korotkova & Jakobsson, 2014; Meuillet & Meuillet, 2011; Sjögren et al, 2013). Targeting early steps in the arachidonic acid pathway results in inhibition of the biosynthesis of other prostanoids that are important for normal physiological functions, thereby rendering the patients administering it susceptible to different side effects (Bian et al, 2021; Cheng et al, 2006; Hassan, Abdel Rahman, et al, 2019; Sharma et al, 2019). Targeting the mPGES‐1 catalyzed final step in the arachidonic pathway allows selective inhibition of PGE2 synthesis and thus can exert the desired anti‐inflammatory actions without serious side effects (Cheng et al, 2006; Martin & Jones, 2017; Psarra et al, 2017; Q. Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%